Cancer risk from heavy metal contamination in fish and implications for public health - Richard Tsiwah Cobbinah; Nathaniel Owusu Boadi; Selina Ama Saah; Eric Selorm Agorku; Mercy Badu; Nii Korley Kortei (Scientific Reports)
Abstract This study evaluates heavy metal contamination in fish and its associated health risks, focusing on the implications for global public health. Fish samples were analyzed using advanced techniques, including Inductively Coupled Plasma-Mass Spectrometry (ICP-MS), Atomic Absorption Spectroscopy (AAS) with a hydride generator for arsenic, and a mercury analyzer. Results revealed significant contamination levels, with arsenic concentrations ranging from 0.9 ± 0.1 to 3.2 ± 0.2 mg/kg (mean: 2.24 ± 0.76 mg/kg), exceeding the WHO limit of 2 mg/kg in 75% of samples. Mercury concentrations (mean: 1.4917 mg/kg) surpassed the WHO limit of 0.5 mg/kg in all samples, while cadmium levels sometimes exceeded permissible limits. Statistical analysis indicated substantial variability in metal concentrations among samples, supported by Principal Component Analysis and Pearson’s correlation, identifying distinct pollution patterns and sources. Health risk assessments showed significant non-carcinogenic and carcinogenic risks, particularly for children. Arsenic, chromium, and mercury presented hazard quotients exceeding safe thresholds, with cumulative hazard indices confirming elevated risks (HI = 14.5 for adults, 44.1 for children). The findings suggest the pressing need for global strategies to monitor and manage heavy metal pollution in aquatic ecosystems.